Sol-Gel Synthesized Nickel-Oxide-Based Fabrication of Arsenic (As3+) Sensor - Ali Alsalme; Huda Alsaeedi; Malak Faisal Altowairqi; Rais Ahmad Khan; Ghadah M. Alharbi; Afnan A. Alhamed (Inorganics, 2023)
Heavy metal ions can have a negative impact on human health when they are present in the environment and diet. In order to enhance healthcare globally, simple, dependable, sensitive, rapid, and accurate technologies for their detection must be created. Herein, we report a sol-gel preparation of nickel oxide (NiO) nanoparticles. The prepared NiO nanoparticles are extensively characterized by PXRD, SEM, and EDS approaches. The obtained SEM results showed that NiO has a nanosphere-shaped surface morphology. The surface area of a gold electrode (Au) was fabricated with NiO nanoparticles via the drop-casting method. The fabricated electrode with NiO nanoparticles (NiO/Au) was applied as an arsenic sensor. The NiO/Au exhibits decent sensitivity of 3.10 µA/ppb and a limit of detection of 1.94 ppb. The NiO/Au also shows good sensing performance for arsenic detection, which includes good stability, repeatability, and selectivity. So far, this is the first report which adopted two electrochemical techniques (cyclic voltammetry and linear sweep voltammetry) for the detection of arsenic using NiO/Au.